2009
DOI: 10.1002/ajhb.20963
|View full text |Cite
|
Sign up to set email alerts
|

Adult health outcomes and their implications for experiences of childhood nutritional stress in Jamaica

Abstract: With insights from the developmental origins of health and disease paradigm (DOHaD), this study explores the impact of childhood nutritional stress on adult health outcomes in Jamaica. Jamaica experienced a lengthy period of political and economic instability beginning in the postcolonial period of the early 1960s. This study tests whether decreased government spending on public resources and limited access to imported food products during the early postcolonial period will be reflected in increased adiposity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…Correlations between age and SoS were not significant and quite small compared to our 95% confidence intervals, suggesting that if there is a small effect, it would require a very large sample size to distinguish it from zero. As expected from the literature ((Nelson, 2009; Wells, Griffin, & Treleaven, 2010), we find BMI and body fat increase with age. We also found that our measurement of frame size, wrist breadth, also increased with age.…”
Section: Discussionsupporting
confidence: 91%
“…Correlations between age and SoS were not significant and quite small compared to our 95% confidence intervals, suggesting that if there is a small effect, it would require a very large sample size to distinguish it from zero. As expected from the literature ((Nelson, 2009; Wells, Griffin, & Treleaven, 2010), we find BMI and body fat increase with age. We also found that our measurement of frame size, wrist breadth, also increased with age.…”
Section: Discussionsupporting
confidence: 91%
“…We should also remember that developmental and epigenetic influences mediated through the environment (socioeconomic and otherwise) can also impact individuals in later life and, through this route, affect their susceptibility to pathogens (Conching & Thayer, 2019; Nelson, 2009; Wells, 2016). South Asians, for example, are suggested to have a particular thin‐fat phenotype in response to long‐standing conditions of fetal under‐nutrition that render them particularly vulnerable to metabolic disorders in later life (Yajnik et al, 2003.…”
Section: Figurementioning
confidence: 99%
“…This research paradigm arose from epidemiological observations connecting low birth size and early postnatal life circumstances to increased risk of cardiovascular disease later in life and other negative adult health outcomes (Barker, 2012; Barker & Osmond, 1986). This research paradigm has been taken up by bioarchaeologists and human biologists to capture the relationship between intrauterine and postnatal “stress” events with morbidity and mortality later in life (eg, Armelagos, Goodman, Harper, & Blakey, 2009; Benyshek, 2013; Garland, 2020; Gowland, 2015; Kuzawa & Sweet, 2009; Lucock et al, 2019; Nelson, 2009; Weisensee, 2013). In the context of LHT and growth outcomes, DOHaD provides an explanatory framework for the potential costs of stress‐induced growth disruptions across the life course.…”
Section: Introductionmentioning
confidence: 99%